Rethinking Konsep Poligami: Menggagas Teologi Sosial dalam Konteks Hukum Keluarga Islam dan Pendidikan Islam - Burhanuddin; Ulyan Nasri (Al-Munawwarah : Jurnal Pendidikan Islam, 2021)
This research aims to reconsider the concept of polygamy in Islam, with a focus on the development of social theology within the context of Islamic family law and Islamic education. In traditional perspectives, polygamy is often narrowly interpreted, without considering the potential social, economic, and educational impacts. In an effort to redefine the concept of polygamy, this research analyzes various written works and views of prominent scholars in Islam. The research attempts to embrace a broader and more holistic perspective on polygamy, involving social theology as a key analytical tool. This approach allows us to examine the social implications of polygamous practices, including issues such as gender equality, women's rights, and their influence on the education of children within polygamous families. The research method employed is qualitative library research. The results of this study will provide fresh insights into how polygamy can be understood within the context of Islamic family law and Islamic education, while highlighting the importance of considering the social aspects associated with this practice. This research is expected to provide a stronger foundation for discussions about polygamy in modern Muslim society and promote a deeper understanding of its implications within the social and educational context.